Adventitious root formation confers waterlogging tolerance in cowpea (Vigna unguiculata (L.) Walp.) - Basavaraj, P. S.; Jangid, Krishna Kumar; Babar, Rohit; Gangana Gowdra, Vinay M.; Gangurde, Anuja; Shinde, Shweta; Tripathi, Kuldeep; Patil, Deepak; Boraiah, K. M.; Rane, Jagadish; Harisha, C. B.; Halli, Hanamant; et al. (Frontiers in Sustainable Food Systems, 2024)
Crop adaptation to waterlogging stress necessitates alterations in their morpho-physiological and biochemical characteristics. Cowpeas, which serve as a dual-purpose legume crop (food and fodder), are sensitive to waterlogging stress, especially when exposed to extended periods of water stagnation during the early growth stage. In this study, we subjected five distinct and superior cowpea varieties to 10 days of waterlogging stress at the early seedling stage (V2, 15 days post emergence for 10 days) under controlled conditions. The aim was to comprehend the response of these varieties and identify the ideal trait for screening a large collection of cowpea genetic resources for waterlogging tolerance. We measured and analyzed changes in morpho-physiological and root parameters to gain a deeper understanding of the mechanism underlying waterlogging tolerance. The treatment (waterlogging and control), genotype, and their interactions had a significant impact on the most studied traits (p < 0.05). The results indicated a significant reduction in morpho-physiological parameters such as plant height, leaf area, leaf number, Normalized Difference Vegetation Index (NDVI), chlorophyll content, and chlorophyll fluorescence parameters under stress treatment than control conditions. However, root parameters like the number of adventitious roots (AR) and their length (ARL) significantly increased under waterlogging stress in tolerant cowpea varieties like DC15 and PL4. Correlation and PCA analyses further revealed a positive and significant association between cowpeas’ waterlogging tolerance and AR formation and its AR length. Therefore, the current study reveals that swift development of AR and ARL may serve as potential traits conferring waterlogging tolerance in cowpeas. Using suitable mapping populations, these traits could reveal genomic regions associated with waterlogging tolerance in cowpeas. The tolerant varieties and key traits identified in this study could be beneficial in breeding programs aimed at enhancing waterlogging tolerance in cowpeas.